Population differences in antibody response to SARS‐CoV‐2 infection and BNT162b2 vaccination. Issue 4 (3rd March 2022) - Shapira, Guy; Abu Hamad, Ramzia; Weiner, Chen; Rainy, Nir; Sorek‐Abramovich, Reut; Benveniste‐Levkovitz, Patricia; Rock, Rachel; Avnat, Eden; Levtzion‐Korach, Osnat; Bar Chaim, Adina; Shomron, Noam
Abstract: The concentration of SARS‐CoV‐2‐specific serum antibodies, elicited by vaccination or infection, is a primary determinant of anti‐viral immunity, which correlates with protection against infection and COVID‐19. Serum samples were obtained from 25 897 participants and assayed for anti‐SARS‐CoV‐2 spike protein RBD IgG antibodies. The cohort was composed of newly vaccinated BNT162b2 recipients, in the first month or 6 months after vaccination, COVID‐19 patients and a general sample of the Israeli population. Antibody levels of BNT162b2 vaccine recipients were negatively correlated with age, with a prominent decrease in recipients over 55 years old, which was most significant in males. This trend was observable within the first month and 6 months after vaccination, while younger participants were more likely to maintain stable levels of serum antibodies. The antibody concentration of participants previously infected with SARS‐CoV‐2 was lower than the vaccinated and had a more complex, non‐linear relation to age, sex and COVID‐19 symptoms. Taken together, our data supports age and sex as primary determining factors for both the magnitude and durability of humoral response to SARS‐CoV‐2 infection and the COVID‐19 vaccine. Our results could inform vaccination policies, prioritizing the most susceptible populations for repeated vaccination.